Qualidade de população de campo do parasitoide Cotesia flavipes Cameron, 1891 (Hymenoptera: Braconidae) - Cabral, Eder de Oliveira (2021)
The parasitoid Cotesia flavipes Cameron, 1891 (Hymenoptera: Braconidae) was successfully introduced in Brazil from 1974. Since then, no new introductions of the parasitoid have been carried out in Brazil. Thus, due to the concern of the biofactories with the quality of the produced parasitoids, a common practice is to introduce in the mass rearing of the laboratory, a population collected in the field, even without any information about the quality of the introduced population, or even, if the results will be positive. Thus, the objective was to determine whether populations of the C. flavipes parasitoid collected in the field have better biological characteristics and flight activity, to be incorporated into mass breeding in the laboratory, in order to improve the quality of the parasitoids. For that, a population of C. flavipes collected in the field (Pradópolis, SP, Brazil) was studied until the twentieth generation and compared with a population kept in the laboratory for 42 years. The egg to pupa period in the laboratory population was longer in generations 5 and 15 (14.0 days) and in the field population it was shorter over generations, mainly in generation 20 (11.0 days). The field population had a lower number of adults emerged per host in the fifth and tenth generations, but in the twentieth generation it had a higher production of offspring per parasitized host (56.5 parasitoids/host). The results obtained for the flight activity test showed that both the population kept in the laboratory and the population obtained in the field showed a higher percentages of insects classified as walkers than flying (25.7 to 32.3% flying). The population collected in the field has stabilized in the laboratory since the tenth generation. In addition, the results of the biological characteristics, longevity and flight activity of the parasitoids, indicate similar quality between the two populations studied after stabilization of the population collected in the field. Keywords: Biological control, sugarcane, sustainable strategies